Traditional phyto-antidotes used for snakebite by Bagata tribe of Eastern Ghats of Visakhapatnam district, Andhra Pradesh - Reddi*, B. Sandhya Sri; T.V.V. Seetharami (International Multidisciplinary Research Journal, 2011)
The present study highlights the medicinal plants used for treating snakebite by Bagata tribe in Visakhapatnam district, Andhra Pradesh. This paper enumerates the traditional uses of 38 plant species belonging to 36 genera under 27 families that act as antidotes against snakebite. Eleven new practices were also reported.